IMPLEMENTASI PRINSIP TRANSPARANSI DALAM PELAYANAN PUBLIK DI KABUPATEN MAMUJU (STUDI KASUS KANTOR PELAYANAN TERPADU SATU PINTU) - Mukhlis Hannan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2017)
This study aims to describe how the implementation of basic tasks and functions of the Community Empowerment Agency and village governance and the factors that influence the implementation process of the Main Task and the function of the community empowerment body of the village government in the Mamuju District. The type of research used in this study is qualitative deskriktif with the basis of survey research. The results showed that the implementation of some program results can be quite good although there are some activities have not achieved the targeted results of the problems faced by BPMPD mamuju district in the implementation of the affairs of community and village government, the improvement of organizational performance that carried out it becomes an absolute thing done Systematic and Structured.